Estructura y funciones del área administrativa, financiera y atención al usuario. Diseño de un sistema alternativo, orgánico funcional y su manual de funciones para la unidad educativa ” Ramón Barba Naranjo. - León Cardenas, Jenny Elizabeth (2015)
The research deals with the design of a Functional Organic Alternative System and User Functions at the Technological Institute "Ramón Barba Naranjo", its impact on the structure and functions of administrative, financial and customer service area, and its general objective analysis of the functioning and structure of the Institute, the organizational and functional institutional development. It was assumed for research A quantitative approach - qualitative and modalities of library research - documentary field and social intervention. The investigations and interviews which allowed identify problems that occur in the institution to seek possible solutions as was done: having a structural and functional organic updated so that all elements have clearly defined their activities and objectives; a manual of functions containing strategies and guidelines for the proper development of the functions of the employees, it will become a great support for financial management and customer service areas and thus fulfill the institutional objectives designed.